The effect of dietary estrogens and acupuncture combined with exercise or exercise alone on bone mineral density in adolescent female athletes suffering from the female athlete triad: A randomized clinical trial - Abd-Elfattah, Hanaa Mohsen; Reda Sakr, Hend; Morsi Galal, Dina Othman Shokri; Abdelkhalek, Mona; Hazim Abbassy, Amr; Emam Elnegamy, Tamer (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study was to investigate the effect of dietary estrogens and acupuncture combined with exercise or exercise alone on bone mineral density in adolescent female athletes suffering from the female athlete triad. A single blind randomized controlled trial was carried out. A total of 44 girls (in adolescence age) diagnosed with low BMD (bone mineral density) resulting from female athlete triad participated in this study. They were divided into three equal groups (group A, B and C). Group A (n = 15) received estrogen from dietary origin in the form of soy milk or soybeans daily in the breakfast combined with weight bearing (WB) exercises. Group B (n = 15) received acupuncture therapy on the acupoints responsible for bone density according to Chinese meridians combined with WB exercises, while group C (n = 14) received WB exercises only. The program was given for 45-60 min/session, three sessions per week for 24 weeks. Z score by Dual-energy X-ray absorptiometry (DEXA) for bone mineral density (BMD) assessment and estradiol 2 (E2) for measuring serum estrogen in blood were measured before treatment and after 24 weeks of treatment. The study groups were comparable on all outcome measures. Within-group comparison showed statistically significant improvements in all measured variables (p < 0.05). Further, between-groups comparison revealed statistically significantly higher improvements in the measured variables, in favor of group B (p < 0.05). The acupuncture sessions combined with WB exercises may be effective in improving bone mineral density in female athlete triad, rather than diet modification by adding soy phytoestrogen in meals beside exercise or exercise alone.